Seasonality in Smoking Behaviour: Re-evaluating the Effects of the 2005 Public Smoking Ban in Italy - Emilia Del Bono; Klaus Grünberger; Daniela Vuri (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper investigates the impact of the public smoking ban which came into effect in Italy on January 2005 on individual smoking behaviour. Current empirical evidence supports the existence of a negative effect of the Italian ban on smoking prevalence and consumption in the general population. This is in contrast to what has been found in some other European countries. Our analysis shows that the apparent success of the Italian smoking ban is due to the fact that existing results do not take into account seasonal differences in smoking behaviour. Using quarterly data from the 1999/2000 and 2004/2005 Italian Health Surveys and adopting a difference-in-difference approach that nets out monthly variation in smoking rates, we show that the Italian smoking ban had no impact on individual smoking behaviour for the population as a whole, and only small effects on some groups of individuals.
Keywords: I12; I18; K32; C31; 330; smoking; cigarette consumption; public smoking ban; treatment effects